The Importance of Wnt Signaling in Cardiovascular Development - Tian, Ying (2009)
Cardiac development is comprised of a series of morphological events tightly controlled both spatially and temporally. The molecular pathways controlling early cardiac differentiation are poorly understood, but Wnt signaling is emerging as a critical pathway for multiple aspects of early cardiovascular development. The Wnt pathway plays multiple roles in regulating cellular behavior including proliferation, differentiation, cell migration, and cell polarity. Recent data have demonstrated that Wnt activity is important for early precardiac mesoderm differentiation but must be inhibited in subsequent steps for cardiomyocyte differentiation to proceed. Given the important role that Wnt signaling plays in both the differentiation of cardiomyocytes from pluripotential stem cells and tissue regeneration in general, an increased understanding of this pathway is likely to enhance our knowledge about both cardiovascular development and reparative mechanisms.